2014
DOI: 10.4103/1305-7456.130581
|View full text |Cite
|
Sign up to set email alerts
|

Effects of antioxidants on the microleakage of composite resin restorations after external tooth bleaching

Abstract: Objective:To compare the effects of three antioxidants (sodium ascorbate, sodium ascorbate combined with a surfactant, and catalase) on the microleakage of composite resin restorations after external tooth bleaching with 10% carbamide peroxide.Materials and Methods:Buccal cavities were prepared on the surface of 60 intact premolars, which were randomly divided into six groups. All cavities were filled with composite resin. In group 1, teeth were not bleached; in group 2, cavities were filled immediately after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 21 publications
(53 reference statements)
1
14
0
2
Order By: Relevance
“…evaluated the effects of antioxidants after bleaching and its influence on the microleakage of composite restorations and concluded that catalase was more effective in reducing microleakage associated with reduced bond strength. [ 24 ] In this study, we used various antioxidants for the evaluation of reversal of bond strength of enamel. Vitamin E, Vitamin C, and SOD are natural antioxidants which can deactivate free radicals.…”
Section: Discussionmentioning
confidence: 99%
“…evaluated the effects of antioxidants after bleaching and its influence on the microleakage of composite restorations and concluded that catalase was more effective in reducing microleakage associated with reduced bond strength. [ 24 ] In this study, we used various antioxidants for the evaluation of reversal of bond strength of enamel. Vitamin E, Vitamin C, and SOD are natural antioxidants which can deactivate free radicals.…”
Section: Discussionmentioning
confidence: 99%
“…[ 16 ] Various research articles have reported diminished bond strength of the composite restorations to enamel following bleaching. [ 3 12 17 18 19 20 21 ] However, to date, relatively few studies have researched on the increase in the microleakage of composite resin restorations following tooth bleaching, specifically external tooth bleaching. [ 12 ]…”
Section: Discussionmentioning
confidence: 99%
“…The present study demonstrated that external bleaching with 35% hydrogen peroxide (Groups II–V) significantly increased the microleakage values of restorations compared to the unbleached group (Group I) [ Table 3 ], which was in accordance with a study done by Han et al . [ 12 ] The presence of residual peroxide and oxygen postbleaching is the main reason for this increase in microleakage. [ 7 8 9 ] Titley et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 25 ] Furthermore, studies have shown the increase of MM due to margins located bellow the CEJ,[ 5 6 7 ] and after external bleaching with 10% carbamide peroxide. [ 27 ]…”
Section: Discussionmentioning
confidence: 99%